Developmental Changes in Children’s Processing of Redundant Modifiers in Definite Object Descriptions - Koolen, Ruud; Krahmer, Emiel; Swerts, Marc (Frontiers in Psychology, 2016)
This paper investigates developmental changes in children’s processing of redundant information in definite object descriptions. In two experiments, children of two age groups (six or seven, and nine or ten years old) were presented with pictures of sweets. In the first experiment (pairwise comparison), two identical sweets were shown, and one of these was described with a redundant modifier. After the description, the children had to indicate the sweet they preferred most in a forced-choice task. In the second experiment (graded rating), only one sweet was shown, which was described with a redundant color modifier in half of the cases (e.g., “the blue sweet”) and in the other half of the cases simply as “the sweet”. This time, the children were asked to indicate on a 5-point rating scale to what extent they liked the sweets. In both experiments, the results showed that the younger children had a preference for the sweets described with redundant information, while redundant information did not have an effect on the preferences for the older children. These results imply that children are learning to distinguish between situations in which redundant information carries an implicature and situations in which this is not the case.